Investigate the Actor’s Dramaturgy: theatre anthropology and its scientific applications - Sastre, Martín Fons (Revista Brasileira de Estudos da Presença, 2022)
Since the birth of Odin Teatret, Eugenio Barba had in mind the quest into the techniques of the actor and his or her ongoing training to reach optimal levels of stage presence. As a result of such interest, the International School of Theatre Anthropology (ISTA) emerged in 1979, giving rise to Theatre Anthropology as a new discipline for the study the fundamentals of acting. This article presents the analysis of the methodological approaches developed by Theatre Anthropology throughout these forty years and its possible connections with other fields of scientific knowledge, highlighting its historiographic, ethnoscenological and neuroscientific applications, for the study of the actor’s pre-expressive principles and the dramaturgical strategies that configure his or her scenic bios.